Analisis Program Kemitraan dalam Meningkatkan Reseller Engagement Evermos - Nazhara Putri Yasyfa; Chandra Hendriyani; Fenny Damayanti (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
The partnership program is one of the company's strategic efforts to increase revenue in order to achieve a sustainable company. Evermos as one of the social commerce that implements a partnership program to increase reseller engagement. The purpose of this study is to analyze the partnership program in increasing reseller engagement at Evermos. This research method is a descriptive qualitative method using interviews, observations, and secondary data. The results show that the partnership program can increase reseller engagement on Evermos. The growth of resellers from year to year can show that the partnership program can increase company profits and a good corporate image. Evermos carries out coaching and training purposes to improve quality, quantity, and open new business opportunities for resellers to sell various kinds of Muslim products in Indonesia without capital. The author provides suggestions to improve quality in providing partnership programs for partners who will work together in order to increase profits and a good image for the company.